Pitch like Hollywood : what you can learn from the high-stakes film industry - Desberg, Peter; Davis, Jeffrey (Professor of screenwriting) (McGraw Hill, 2022)
"A clinical psychologist and writer/producer share secrets to overcoming presentation anxiety and crafting the perfect "award-winning" pitch-no matter what industry you work in! From impromptu elevator pitches to full-board presentations, sales and marketing professionals face an "audience" daily-often with make-or-break consequences. No matter what business you're in, you can up your game substantially by incorporating elements of a classic Hollywood pitch: driving emotion, piquing curiosity, and ultimately winning over decision makers with top-notch persuasion and performance. Pitch Like Hollywood, clinical psychologist Peter Desberg and writer/producer Jeffrey Davis take you on an insiders' tour of the entire process, from defining the fundamentals to smart strategies for overcoming stage fright (pitch panic). They also include a step-by-step guide so that you can adapt the Hollywood Pitch for your next board meeting or sales call. With chapters that include Persuasion Boot Camp, The Pitch Panic Cycle, and Creating the Pitch II (The Sequel), you'll have a front-row seat in a master class on giving great performances for any audience, every time"--